In vitro and in vivo antifungal efficacy of individual and consortium Bacillus strains in controlling potato black scurf and possible development of spore-based fungicide - Imen Ben Slimene Debez; Amani Ben Alaya; Ines Karkouch; Bilel Khiari; Pedro Garcia-Caparros; Nouf M. Alyami; Ahmed Debez; Belhassen Tarhouni; Naceur Djébali (Biological Control)
Potato is a major crop whose yield and quality are impacted by the pathogenic fungus Rhizoctonia solani. Here, a control approach based on the use of endophytic bacillus spores and bacterial consortia was assessed as an innovative solution to improve tuber productivity and health. Endophytic potato bacteria extracted from several organs (leaves, stems and roots) evaluated for their antagonistic activity against R. solani by the double culture technique and their ability to rot potato slices. Additionally, the ability of Bacillus strains to generate hydrolytic enzymes and produce lipopeptides (using ESI-MS/MS mass spectrometry) was assessed. Then, the effectiveness of selected bacterial strains, either individually or in consortium (after carrying out compatibility tests) in the suppression of R. solani was evaluated in the greenhouse. Six endophytes not affecting potato tubers and having an antagonistic effect against R. solani were identified: B. halotolerans SpS5, B. velezensis KnL15, B. aryabhattai FaR1, B. amyloliquefaciens LiR9, B. haynesii ReR10 which produce several types and combinations of lipopeptides belonging to different families (iturins, fengycins and surfactins) as well as hydrolytic enzymes (chitinase, protease and cellulase). The vegetative and sporulating strain SpS5, as well as the 5 other Bacillus and their Sps5-based consortia, were found to be very effective in increasing the yield of healthy, high-quality tubers and reducing disease severity. Based on the results mentioned above, a microbial fungicide from the spores of (i) B. halotolerans SpS5 for which we sequenced the whole genome or (ii) bacterial consortia could be developed to combat black scurf potato and other fungal infections.